Airflow and precipitation structure of two leading stratiform mesoscale convective systems - Pettet, Crystalyne R., author (Colorado State University. Libraries, 2001)
An analysis of the airflow and precipitation structure of two leading stratiform (LS) mesoscale convective systems is presented. LS systems are defined as linear MCSs that consist of a convective line with leading stratiform rain. Case studies of LS systems on 30 April 2000 and 7 May 1997 were conducted using the available operational datasets. Several of the features observed, though not all, appear as a mirror image of those seen in trailing stratiform (TS) mesoscale convective systems. Their horizontal reflectivity structure has similar aspects, with convective cells which are sometimes elongated and canted with respect to the convective line, a transition zone of lower reflectivity, and an area of enhanced stratiform rain. Cold pools are situated beneath the convective line. The 30 April case shows a leading mesolow that resembles a TS wake low, but its propagation characteristics (and presumably dynamics) differ. A descending leading inflow jet, the counterpart of a rear inflow jet in a TS system, can be detected in both cases underneath a layer of strong ascending rear-to-front flow aloft. A few features of these LS systems are distinctive from TSs. Cells in the convective line appear to be more discontinuous and are elongated more than those of a TS. Rear feeding from an elevated Be maximum behind the system is an exclusive feature of these LSs, since TSs are typically fed from the boundary layer. Unlike the rear inflow jet in TS systems, neither case shows a reversal in the leading inflow jet as it descends to low levels near the convective line. Both cases exhibit front-to-rear surface flow throughout the LS systems. Finally, a schematic diagram is presented that illustrates the structure observed in the two cases, based heavily on a Doppler radar analysis of 7 May 1997.
Fall 2001.
Also issued as author's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Convection (Meteorology); Atmospheric circulation; Precipitation (Meteorology)